Neurological soft signs in autism spectrum disorder (Panacea Journal of Medical Sciences, 2022)
Background: Autism spectrum disorder (ASD) is a phenotypically heterogeneous group of neurodevelopemental syndromes characterized by impairments in social communication and restricted & repetitive behavior. Neurological soft signs (NSS) are minor neurological abnormalities that aren’t a part of any fixed/transient neurological disorders. The most common NSS in ASD are motor incoordination, difficulty sequencing motor tasks & sensory disintegration.Materials and Methods: 22 participants of ASD satisfying the inclusion and exclusion criteria were assessed for NSS, using a semi structured performa & Heidelberg manual for neurological soft signs. The data was tabulated and analysed statistically.Results: The mean age of the participants was 11.63 years with 82% males & 18% females. 100% participants had dysdiadochokinesia (82% -adiadochokinesia), errors in the finger-nose test(71% unable to perform), right-left confusion (39% -making gross errors), difficulty in tandem walking(70% -significant balance problems), difficulty in fist-edge-palm (54% unable to complete task) & ozeretski test (78%- unable to perform). 94% had difficulty in pronation-supination (56%-failed to complete exercise).89% of the participants had difficulty in finger –thumb opposition (63%- unable do it).Conclusion: NSS are present in a significant amount of patients of ASD & such patients should be assessed for the full spectrum of NSS.